1995
DOI: 10.1177/43.9.7642960
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity diagnosis of AA amyloidosis using Congo red and immunohistochemistry detects missed amyloid deposits.

Abstract: Biopsy diagnosis of early amyloid-A (AA) amyloidosis has often been difficult. Examination of 57 consecutive biopsy specimens from 42 patients with inflammatory pediatric diseases permitted comparison of the precision of biopsy amyloid diagnosis in six different laboratories (labs), which applied the following methods: Congo red alone (four unspecialized labs combined as Lab 1), Congo red and electron microscopy (Lab 2), or Congo red and immunohistochemistry using monoclonal antibodies (Lab 3). Lab 3 reexamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 4 publications
(4 reference statements)
3
41
0
1
Order By: Relevance
“…Immunohistochemistry is usually definitive in identifying or ruling out AA amyloidosis, but it frequently is not diagnostic with respect to AL amyloidosis. 8,21 In our series, AL fibrils were identified by immunohistochemical staining in only 121 of the 316 patients with confirmed AL disease (38 percent). This reflects the failure of anti-light-chain antibodies to bind to light-chain fragments with an abnormal cross-b amyloid-fibril conformation and also reflects background staining of normal immunoglobulins in the tissues.…”
Section: Discussionmentioning
confidence: 60%
“…Immunohistochemistry is usually definitive in identifying or ruling out AA amyloidosis, but it frequently is not diagnostic with respect to AL amyloidosis. 8,21 In our series, AL fibrils were identified by immunohistochemical staining in only 121 of the 316 patients with confirmed AL disease (38 percent). This reflects the failure of anti-light-chain antibodies to bind to light-chain fragments with an abnormal cross-b amyloid-fibril conformation and also reflects background staining of normal immunoglobulins in the tissues.…”
Section: Discussionmentioning
confidence: 60%
“…8 In a study, immunohistochemical analysis was reported as a helpful method to evaluate the overlooked or trace deposits of amyloidosis. 16 In this study, Congo Red method (Liebs and Bennhold's methods) for amyloid A staining was used for the evaluation of amount, localization, and type of glomerular accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the durability of this assay, the optical characterization of amyloid has not progressed and is ambiguous (8,9). The birefringence is rarely quantified, a problem further confounded by the fact that CR does not stain amyloid consistently, and diagnosis by staining depends on the skill of the investigator.…”
mentioning
confidence: 99%